2019
DOI: 10.3390/ijerph16020257
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Contamination on Latrine Surfaces in Community and Household Latrines in Kathmandu, Nepal

Abstract: A lack of sanitation infrastructure is a major contributor to the global burden of diarrheal disease, particularly in low-income countries. Access to basic sanitation was identified as part of the 2015 United Nations Sustainable Development Goals. However, current definitions of “basic” sanitation infrastructure exclude community or shared sanitation, due to concerns around safety, equity, and cleanliness. The purpose of this study was to measure and compare bacterial contamination on community and household l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 20 publications
1
16
0
6
Order By: Relevance
“…European Journal of Health Sciences ISSN 2520-4645 (online) Vol.5, Issue1, pp 1- 11,2020 www.ajpojournals.org 4…”
Section: Research Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…European Journal of Health Sciences ISSN 2520-4645 (online) Vol.5, Issue1, pp 1- 11,2020 www.ajpojournals.org 4…”
Section: Research Objectivementioning
confidence: 99%
“…Test for Gram positive bacteria included penicillin (1.5µg), ampicillin (10µg), cloxacillin (5µg), erythromycin (5µg), tetracycline (30µg), vancomycin (30µg), cotrimoxazole (25µg), cefuroxime (10µg), gentamicin (10µg), ciprofloxacin (5µg), augmentin (30µg) and meropenem (10µg). Test for Gram European Journal of Health Sciences ISSN 2520-4645 (online) Vol.5, Issue1, pp 1- 11,2020 www.ajpojournals.org 5 negative bacteria included ampicillin (10µg), tetracycline (10µg), cotrimoxazole (10µg), gentamicin (10µg), cefuroxime (30µg), vancomycin (30µg), chloramphenicol (10µg), ceftriaxone (30µg), cefotaxime (30µg), ciprofloxacin (5µg), amikacin (30µg) and meropenem (10µg). Controls were set using Escherichia coli ATCC 25922 and Staphylococcus aureus ATCC 29213.…”
Section: Antimicrobial Susceptibility Testingmentioning
confidence: 99%
“…Contact surface contamination within the toilet facilities was widespread (Figure 3), despite a higher prevalence of contamination on the tap handles, the floor of these toilets and the internal latch of the toilet cubicles. Several studies have reported similar findings in relation to the most contaminated surfaces in toilet facilities 48,49,50,51,52,53,54 . Notably, Fankem et al 48 , observed that the most contaminated surfaces in public toilets found in airports, bus terminals, and universities were the sanitary napkin dispensers, toilet seats, sinks, and floors.…”
Section: Discussionmentioning
confidence: 56%
“…Based on our study results, at least for the two markets with working sanitation facilities, the sanitation facilities were probably sufficient for users, whereas at the two other markets, this infrastructure should be immediately prioritized. McGinnis, Marini, Amatya, and Murphy () noted that well‐maintained privately owned, pay‐per‐use community sanitation facilities in Nepal were as clean or cleaner than household sanitation facilities. Based on the swab sample results for bacterial concentrations in that study, in community sanitation facilities, the seat/floor, tap/handle/bucket used for anal cleansing, and door handles were the surfaces to focus on when cleaning.…”
Section: Discussionmentioning
confidence: 99%